Optimalisasi Usaha Kuliner di Obyek Wisata Hiu Paus Desa Botu Barani Kabupaten Bone Bolango, Gorontalo - Krishna Anugrah (Universitas Merdeka Malang, 2018)
This study focused about optimalization culinary product small scale, which is owned by local community. Before the existing of whale shark the most occupation of local community as a fisherman. Many tourist come interested to see the existing of whale shark. with the presence of whale sharks, it is an additional opportunity for fishermen to increase their income. When they don't go fishing catch fish then they rent boats owned by tourists to see the existence of whale sharks. Whale shark attraction has several facilities which is managed by local community, visitor who has come and want to see whale shark attraction must by boat ticket. One of the facilities is culinary product in small scale. These culinary product has potential revenue for local community to get more income. Tourist spend about 1-2 hour to see the whale shark. This duration has good potential for local community to offer their culinary product to all visitor. In an effort to increase culinary business income, cooperation with other parties is needed. Such cooperation is like cooperating with related parties, which is at the ticket ticket sales booth by selling the package price with the food and drinks provided. in an effort to increase culinary business income, cooperation with other parties is needed. Such cooperation is like cooperating with related parties, which is at the ticket ticket sales booth by selling the package price with the food and drinks provided.